The Effectiveness of the Discovery Learning Model in Fiqh Learning in Madrasah - Zubaedi, Muhammad (Journal of Education and Religious Studies, 2025)
This research article aims to determine the effectiveness of the Discovery Learning Model in fiqh learning in Madrasah, this research article uses Classroom Action Research (PTK) which is studied on grade VIII students of MTs Mamba'us Sholihin Suci Manyar Gresik in 2024 consisting of four stages, namely; planning, action, observation, reflection. The data collection method uses observation, documentation, tests and interviews. The results of this study show a significant increase in students' critical and collaborative thinking. The percentage of students' critical thinking in the pre-cycle was 48%, cycle I was 65%, cycle II meeting I increased to 85%, cycle III increased to 95%. The student learning outcomes obtained in the first cycle were 84.55%, but in the second cycle it was 89.25%, in the third cycle the implementation of Discovery Learning was increased again so that the percentage obtained increased to 97.55%. The application of the Discovery Learning model can improve Learning Outcomes by making modifications in terms of; the use of attractive media, seating arrangements, and effective classroom management strategies